Review of the Marital Satisfaction Scale’s Factor Structure - José Augusto Evangelho Hernandez (Temas em Psicologia, 2017)
Marital satisfaction is a construct that is relevant to psychology research due to its significance in terms of establishing this interpersonal relationship. The present study examines the factor structure of the Marital Satisfaction Scale (MSS). The MSS has frequently been employed in Brazilian studies, incorporated as a convergent measure for producing criterion validity evidence in the elaboration of new psychometric methods. Nonetheless, its psychometric properties have not been substantiated for 25 years. A non-probabilistic sample of 249 people from Rio de Janeiro participated in the present study, their ages ranging between 21 and 77 years (M = 45.3; SD = 13.26). They had been married or involved in a civil union (also known as a “domestic partnership” or “common-law marriage” depending on the location) for an average of 19.5 years (SD = 12.88). The collected data was assessed via exploratory and confirma tory factor analyses. Such assessment revealed several items exhibiting poor psychometric performance. Nevertheless, an abridged version of the MSS provided simplicity and produced excellent fit indices. It also yielded validity evidence of the existence of a second-order factor. The estimated reliability for both the factors and the entire scale ranged between 0.85 and 0.93.